Perspectives on Risk, Assessment and Management Paradigms - Hessami, Ali G. (IntechOpen, 2019)
This book explores various paradigms of risk, domain-specific interpretation, and application requirements and practices driven by mission and safety critical to business and service entities. The chapters fall into four categories to guide the readers with a specific focus on gaining insight into discipline-specific case studies and state of practice. In an increasingly intertwined global community, understanding, evaluating, and addressing risks and rewards will pave the way for a more transparent and objective approach to benefiting from the promises of advanced technologies while maintaining awareness and control over hazards and risks. This book is conceived to inform decision-makers and practitioners of best practices across many disciplines and sectors while encouraging innovation towards a holistic approach to risk in their areas of professional practice.